Informatics in control, automation and robotics : 10th International Conference, ICINCO 2013 Reykjavík, Iceland, July 29-31, 2013 Revised selected papers /: 10th International Conference, ICINCO 2013 Reykjavík, Iceland, July 29-31, 2013 Revised selected papers. ([2014]) - Unknown
No abstract available